2022
DOI: 10.3390/plants11070886
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Activates Antioxidant Systems to Increase the Ability of Rice Seeds to Germinate under High Temperature Conditions

Abstract: High temperatures are a major concern that limit rice germination and plant growth. Although previous studies found that melatonin can promote seed germination, the physiological regulation mechanism by which exogenous melatonin mediates high temperature tolerance during rice seed germination is still largely unknown. In order to overcome these challenges, the present study investigates the effects of melatonin on the characteristics of rice seed germination as well as on antioxidant properties, under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…It also enhanced the activities of antioxidant enzymes, protein, and lipid molecules and favored the lower production of H 2 O 2 and MDA 74 Strawberry ( Fragaria × ananassa Duch.) 35°C and 40°C 0, 50, and 100 μM MET treatment decreased heat injury symptoms and induced antioxidant mechanisms, also up-regulated the expression of defense HSF ( FaTHsfA2a, FaTHSFB1a ) and HSP ( HSP90 ) genes 75 Rice ( Oryza sativa L.) 38 ◦C 0, 20, 100, 500 µM MET treatment improved the heat tolerance of rice seeds by enhancing the activity of the antioxidant enzymes and significantly reducing the MDA content 76 Tomato ( Solanum lycopersicum L.) 40°C, 7 d 50 mM MET alleviated the oxidative damage of PSII by balancing the electron transfer of the donor side, reaction center, and receptor side 77 Rice ( Oryza sativa L.) 38°C/28°C 250 mL of 200 μmol L −1 MET improved the stress resistance by enhancing the scavenging efficiency of ROS and improved the leaf photosynthetic and heat-resistance properties. 78 Abbreviations: Abscisic acid (ABA); ascorbate peroxidase (APX); cold stress (CS); cytokinin (CK); chlorophyll (Chl); catalase (CAT); glutathione reductase (GSSG-R); gibberellic acid (GA3); heat stress (HS); hydrogen peroxide (H 2 O 2 ); heat shock proteins (HSPs); indole-3-acetic acid (IAA); malondialdehyde (MDA); melatonin (MET); peroxidase (POD); reactive oxygen species (ROS); superoxide dismutase (SOD); zeatin (ZT).…”
Section: Potential Of Exogenous Melatonin In Managing Temperature Str...mentioning
confidence: 99%
“…It also enhanced the activities of antioxidant enzymes, protein, and lipid molecules and favored the lower production of H 2 O 2 and MDA 74 Strawberry ( Fragaria × ananassa Duch.) 35°C and 40°C 0, 50, and 100 μM MET treatment decreased heat injury symptoms and induced antioxidant mechanisms, also up-regulated the expression of defense HSF ( FaTHsfA2a, FaTHSFB1a ) and HSP ( HSP90 ) genes 75 Rice ( Oryza sativa L.) 38 ◦C 0, 20, 100, 500 µM MET treatment improved the heat tolerance of rice seeds by enhancing the activity of the antioxidant enzymes and significantly reducing the MDA content 76 Tomato ( Solanum lycopersicum L.) 40°C, 7 d 50 mM MET alleviated the oxidative damage of PSII by balancing the electron transfer of the donor side, reaction center, and receptor side 77 Rice ( Oryza sativa L.) 38°C/28°C 250 mL of 200 μmol L −1 MET improved the stress resistance by enhancing the scavenging efficiency of ROS and improved the leaf photosynthetic and heat-resistance properties. 78 Abbreviations: Abscisic acid (ABA); ascorbate peroxidase (APX); cold stress (CS); cytokinin (CK); chlorophyll (Chl); catalase (CAT); glutathione reductase (GSSG-R); gibberellic acid (GA3); heat stress (HS); hydrogen peroxide (H 2 O 2 ); heat shock proteins (HSPs); indole-3-acetic acid (IAA); malondialdehyde (MDA); melatonin (MET); peroxidase (POD); reactive oxygen species (ROS); superoxide dismutase (SOD); zeatin (ZT).…”
Section: Potential Of Exogenous Melatonin In Managing Temperature Str...mentioning
confidence: 99%
“…The increase in melatonin alleviated the inhibition of germination and growth of plants, such as Arabidopsis , rice, watermelon, Camellia sinensis , cucumber, tomato, soybean, Chrysanthemum , Actinidia deliciosa , etc. [ 15 , 37 , 38 , 44 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] ( Table 1 ). Similar to salinity and drought stresses, cold or heat stress induced severe oxidative stress, and melatonin increased APX, SOD, CAT, POD, GPX, GR, Gly I, and Gly II activity, as well as GSH, ASC, proline, flavonoid, and proline contents.…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
“…Many studies demonstrated the dose-dependent response of melatonin in plants tolerant to salt ( Ahmad et al, 2021a ), cold ( Chang et al, 2022 ), high temperature ( Yu et al, 2022 ), and heavy metals ( Nabaei & Amooaghaie, 2019 ). Ahmad et al (2019) found that foliar application of 100 µM was more effective in improving maize seedling’s drought tolerance than 50 and 75 µM melatonin application.…”
Section: Discussionmentioning
confidence: 99%